Moderate Intensity of Physical Exercise increased β (Beta) Cell and Size of Langerhans Islets in Streptozotocin Induced Diabetes Mellitus Rats - Nurdin, Sarah M; Nugraheni, Nuniek; Wulan, Mei (Surabaya Physical Medicine and Rehabilitation Journal, 2019)
Background: The death of β cells Langerhans islets in Diabetes Mellitus (DM) can cause  loss of Langerhans islet function and worsen the progression of DM. Physical exercise plays a major part in DM treatment.Aim: to observe the effect of moderate intensity exercise to β (beta) cell numbers and Langerhans islets area size in Streptozotocin (STZ) induced diabetes in rats.Methods: Thirty adult male Wistar rats (Rattusnorvegicus) divided into 3, Group 1 as the control, Group 2 received 35 mg/kg streptozotocin induction treatment, Group 3 received 35 mg/kg streptozotocin induction and physical exercise, swimming, with moderate intensity 70% from the swimming maximal ability, 9% of body weight load, 4 times a week for 4 weeks. Datas collected were in the form of histopathology slide of pancreatic tissue after receiving treatment for 28 days.Results: There are significant differences of β-cell pancreas number between group K1 and K2 (p<0,001), group K2 and to K3 (p<0,001). No significant difference between group K1 and K3 (p=0,102). The Langerhans islets area sizes of pancreas tissue between group K1, K2, and K3 are significantly different (p<0,001).Conclusion: This study shows moderate-intensity physical exercise can increase the number of β cell and average area size of Langerhans islets. The effect of physical exercise depends on the intensity of exercise and the capacity of pancreatic function left of the diabetic.